About Six in Ten Survivors of the November 2020 Maikadra Massacre Suffer from Posttraumatic Stress Disorder, Northwest Ethiopia [Corrigendum] - Ali D; Azale T; Wondie M; Tadesse J (Psychology Research and Behavior Management, 2023)
Ali D, Azale T, Wondie M, Tadesse J. Psychol Res Behav Manag. 2022;15:251–260. The authors have advised there is an error in the author list on page 251. The author name “Melese Wondie” should read “Mesele Wondie.